Drain insertion after appendectomy in children with perforated appendicitis based on a single-center experience - Song, Ra-Yeong; Jung, Kyuwhan (Annals of surgical treatment and research, 2015)
Management of appendicitis in children has always been an issue in pediatric surgery. Both diagnostic methods and treatment vary significantly among medical centers, and little consensus exists in many aspects of the care for patients with appendicitis. Here, we assessed the value of drain insertion after appendectomy in children. This study is a retrospective review of pediatric patients who underwent appendectomy for perforated appendicitis at a tertiary medical center between 2003 and 2012. Patients who had a peritoneal drain inserted after appendectomy were compared with patients without drains regarding preoperative features and postoperative outcomes. Statistical analyses included a 2-tailed Student t-test and a chi-square or Fisher exact test. In total, 958 patients were reviewed. Of 342 patients with perforated appendicitis, 108 (31.6%) had Jackson-Pratt (JP) drains inserted. The JP group had a longer hospital stay compared with the non-JP group (6.38 ± 3.59 days vs. 3.87 ± 2.38 days, P < 0.001). The JP group also had higher complication rates (22.2% vs. 6.8%, P = 0.003), including the formation of intra-abdominal abscesses. According to our results, there seems to be little evidence to support peritoneal drain insertion after appendectomy, even in perforated appendicitis cases.